State of the Art—Auctions and Bidding Models: A Survey - Engelbrecht-Wiggans, Richard (Management Science, 1980)
Auctions and bidding models are attracting an ever increasing amount of attention. The Stark and Rothkopf (Stark, R. M., M. H. Rothkopf. 1979. Competitive bidding: a comprehensive bibliography. Oper. Res. 27 (2) 364–390.) bibliography includes approximately 500 works in the area. Additional work has appeared since the bibliography was compiled. This paper surveys the main theoretical results and research efforts of the literature on auctions and bidding. A framework is presented for classifying and describing various auctions and bidding models based on the types of assumptions made for the models' various parameters. The major works, ideas, and results of the literature are surveyed in terms of this framework.